Propuesta arquitectónica de un centro de interpretación cultural para la parroquia de Yaruquí (Quito - Ecuador). - Estrada Estévez, Oscar Patricio (2025)
After decades, the construction of the railroad connected several provinces of Ecuador, it was used continuously until they decided to abandon it and time carried out its work. This structure has left vestiges throughout the country, as is the case of the parish of Yaruquí in which there is a steel bridge, a tunnel more than 30 meters long that was dug by hand and also a station of stone, wood and steel, it remains standing, but in a very marked deterioration. The present work aims to investigate terms on cultural interpretation, analyze references, compile historical and tourist information of the sector, to propose a and to reform the selected place through an architecture that accompanies the preexistence, this being the railway station, in which it is intended to maintain the essence of the existing module with the preservation of the stone base which is used as a resting and meeting point for the settlers, also maintain a stone wall which gave order to the loading and unloading of animals and also the post that served as a telegraph connection, these decisions were made due to the great impact of the station and its connection with the people of yaruqueño.